P element temperature-specific transposition: a model for possible regulation of mobile elements activity by pre-mRNA secondary structure - Gultyaev, A.; Redchuk, T.; Korolova, A.; Kozeretska, I.P (Цитология и генетика, 2014)
P element is a DNA transposon, known to spread in genome using transposase activity. Its activity is tissue-specific and normally observed at high temperatures within 24°C to 29°C. Here, we present a predicted RNA secondary structure domain of P element pre-mRNA which could potentially regulate the temperature sensitivity of the P element activity. In canonical P elements, the structure is a small hairpin with double-helical part interrupted by a symmetric loop and a mismatch. In M type P elements, the A.A mismatch is substituted by an A-U base pair, stabilizing the structure. The hairpin structure covers the region involving the IVS-3 5′ splice site and both pseudo-splice sites F1 and F2. While the IVS-3 and F1 binding sites of U1 snRNA are located in the double-stranded part of the structure, the F2 site is exposed in the hairpin loop. The formation of this structure may interfere with landing of U1 snRNA on IVS-3 site, while F2 is positioned for the interaction. Alignment of P element sequences supports the proposed existence of the hairpin, showing high similarity for this region. The hairpin structure, stable at low temperatures, may prevent correct IVS-3 splicing. Conversely, temperature-induced destabilization of the hairpin structure may result in the splicing at the proper IVS-3 splice site. Taking into account the increasing amount of data demonstrating the important influence of RNA folding on phenotypes determined by alternative splicing a model for possible regulation of the activity of mobile elements by pre-mRNA secondary structure seems intriguing. Предсказана вторичная структура пре-мРНК P-элемента, которая, возможно, регулирует его активность и температурную чувствительность. Структура представляет собой шпильку, более стабильную в Р-элементах М-типа, в сравнении с каноническими. Регион, образующий шпильку, находится в области 5’ сайта сплайсинга третьего интрона (IVS-3), включая оба описанных псевдо-сайта сплайсинга - F1 и F2. В то время как истинный сайт и F1 расположены, главным образом, в двухцепочечной области шпильки, F2 - экспонирован в петле. Выравнивание последовательностей Р-элементов продемонстрировало высокую степень сходства для указанного региона, что свидетельствует в пользу существования предсказанной структуры. Формирование шпильки, по нашему мнению, может препятствовать связыванию U1 snRNA с истинным сайтом сплайсинга, и, напротив, индуцированная температурой дестабилизация шпильки может приводить к корректному сплайсингу IVS-3. Таким образом, предложена гипотеза о влиянии вторичной структуры пре-мРНК мобильного элемента на его активность. Передбачена вторинна структура пре-мРНК Р-елемента, що, можливо, регулює його активність та температурну чутливість. Структура являє собою шпильку, більш стабільну у Р-елементах М-типу, порівняно з канонічними. Регіон, що утворює шпильку розташований в області 5’ сайта сплайсинга третього інтрону (IVS-3), включає обидва відомих псевдо-сайта сплайсингу - F1 та F2. При цьому 5’ сайт сплайсингу IVS-3 та F1псевдо-сайт знаходяться у дволанцюговій частині шпильки, а F2 є єкспонованим у петлі. Вирівнювання послідовностей Р-елементів продемонструвало високий рівень подібності для вказаного регіону, що свідчить на користь існування передбаченої структури. Формування шпильки, на нашу думку, може перешкоджати зв’язуванню U1 snRNA з 5’ сайтом сплайсингу IVS-3, і, навпаки, індукована температурою дестабілізація шпильки може сприяти корректному сплайсингу третього інтрону. Таким чином, запропонована гіпотеза про вплив вторинної структури пре-мРНК мобільного елементу на його активність.